Comparison and assessment of circumsolar ratio models for Évora, Portugal - Abreu, Edgar F.M. (2020)
The sun rays are scattered due to molecules, aerosols and some cloud types, such as cirrus clouds, and a region near to the vicinity of the sun disk, known as circumsolar region, with relatively high diffuse sky radiance is formed [1]. Consequently, this diffuse radiation is called circumsolar normal irradiance (CSNI). Modelling the CSNI is important because pyrheliometers (the instruments that are used to measure direct normal irradiance – DNI), have an aperture angle wider than the circumsolar region, and thus DNI measurements obtained with these instruments cannot resolve the distribution of solar radiance in that region [2]. Moreover, since concentrated solar power (CSP) systems only capture solar radiation from this region but with a narrower aperture angle than that of the pyrheliometers, this leads to an overestimation of the energy reaching the receiver of the CSP systems [1]. This can result in misleading power output estimations, which can harm the bankability of CSP projects. Information on CSNI is also crucial when designing, sizing and operating CSP powerplants.